An electrolyte and a battery comprising the same

CN116093432BActive Publication Date: 2026-10-23ZHUHAI COSMX BATTERY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310083748.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2026-10-23
Estimated Expiration
2043-02-08

AI Technical Summary

Benefits of technology

[0064]本发明提供了一种电解液及包括该电解液的电池,具有特定O原子和S原子的原子个数比的第一添加剂的引入有利于形成以Li2SO3为主的SEI膜,而该以Li2SO3为主的SEI膜的强度较高、导离子性能较好,能够提升电池的循环性能和存储性能,而且还能抑制溶剂和正负极发生氧化还原反应产生气体,使得所述电解液能够抑制电池产气。进一步搭配具有特定Fe/Si质量比的铝箔,铝箔中存在Fe元素,该元素能够成为催化的催化点,诱导第一添加剂分解,并在铝箔表面形成主要成分为FeSO4的钝化层,该钝化层能够显著抑制电解液在铝箔表面上的催化氧化以及产气。同时,该钝化层能够改善电池的针刺性能,还能显著提升电池的低温性能。综上,通过加入特定含量的添加剂组分,并配合具有特定Fe/Si质量比的铝箔,能够获得具有较好的针刺性能、产气性能、循环性能、储存性能和低温性能的电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The application provides an electrolyte and a battery comprising the electrolyte, the electrolyte comprising an organic solvent, an electrolyte salt and a functional additive; the functional additive comprising a first additive and a second additive, the first additive being an organic small-molecule compound containing S elements and O elements, an atomic number ratio of O atoms to S atoms in the first additive being less than or equal to 4; the second additive being 1,3-propane sulfone; the electrolyte can improve the cycle performance and storage performance of the battery, and can also significantly inhibit the oxidation-reduction reaction of the solvent and the positive and negative electrodes to produce gas, so that the electrolyte can inhibit the gas production of the battery. Further, in combination with an aluminum foil having a specific Fe / Si mass ratio, the Fe element existing in the aluminum foil can improve the needle puncture performance of the battery and also improve the low-temperature performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electrolyte and a battery comprising the electrolyte, belonging to the field of lithium-ion battery technology. Background Technology

[0002] Lithium-ion batteries possess a series of advantages such as long cycle life, high energy density, and low cost, and have been increasingly widely used in various electronic products, electric vehicles, power tools, and energy storage devices in recent years. In particular, with the large-scale application of lithium-ion batteries in electric vehicles, the requirements for battery lifespan are becoming increasingly stringent. As a key material affecting battery life, improvements to the electrolyte can significantly enhance battery performance. Therefore, providing a high-performance electrolyte is a continuous pursuit of those skilled in the art. Summary of the Invention

[0003] This invention provides an electrolyte and a battery comprising the electrolyte. The electrolyte can form a stable SEI film on the surfaces of the positive and negative electrodes, suppressing gas generation in the battery, improving the battery's cycle performance and storage performance, and also improving the battery's needle penetration safety performance. Further combining it with aluminum foil having a specific Fe / Si content ratio can further suppress gas generation in the battery while improving the battery's needle penetration safety performance, and also significantly improve the battery's low-temperature performance.

[0004] The objective of this invention is achieved through the following technical solution:

[0005] An electrolyte comprising an organic solvent, an electrolyte salt, and a functional additive; the functional additive comprising a first additive and a second additive, wherein the first additive is a small organic molecule compound containing sulfur (S) and oxygen (O) atoms, and the ratio of O atoms to S atoms in the first additive is ≤4; the second additive is 1,3-propanesulfonate lactone; the electrolyte satisfies the following relationship:

[0006] 1%≤A+B≤7%, A / B≥0.08;

[0007] Wherein, A is the percentage of the mass of the first additive to the total mass of the electrolyte; B is the percentage of the mass of the second additive to the total mass of the electrolyte.

[0008] According to an embodiment of the present invention, the ratio of O atoms to S atoms in the first additive is ≤3, preferably ≤2. The introduction of a first additive having a specific ratio of O atoms to S atoms is beneficial for forming a Li2SO3-based SEI film, which is conducive to improving battery cycle performance and storage performance.

[0009] According to embodiments of the present invention, A+B is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, or 7%. When 1% ≤ A+B ≤ 7%, the electrolyte can form a Li2SO3-based SEI film on the negative electrode surface. This Li2SO3-based SEI film has high strength and good ion conduction performance, effectively improving the battery's cycle performance and storage performance. It can also effectively suppress the oxidation-reduction reaction of the solvent at the positive and negative electrodes, thus inhibiting gas production in the battery. When A+B > 7%, the content of functional additives is excessive. Although such an electrolyte can inhibit gas production, it has high impedance, leading to a severe deterioration in the battery's cycle performance and storage performance, and also seriously affecting the battery's rate performance and low-temperature performance. When A+B < 1%, the content of functional additives is too low. Such an electrolyte cannot form an effective SEI film on the negative electrode surface and cannot inhibit gas production in the battery.

[0010] According to an embodiment of the present invention, 10 ≥ A / B ≥ 0.1; preferably, 8 ≥ A / B ≥ 0.1. Exemplarily, A / B is any value within the range of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.5, 1.8, 2, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 4.8, 5, 5.2, 5.5, 5.8, 6, 7, 8, 9, 10, or any value within the range of pairs of the above values. When A / B ≥ 0.08, the SEI film formed on the negative electrode surface by the functional additive will contain a relatively large amount of organic components, and the organic components have good ion-conducting properties, which is beneficial to improving the battery's charge and discharge performance.

[0011] According to an embodiment of the present invention, A is 0.5% to 4%, that is, the mass of the first additive accounts for 0.5% to 4% of the total mass of the electrolyte; for example, it is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or any value within the range of the above two-to-one values.

[0012] According to an embodiment of the present invention, B is 0.5% to 5%, that is, the mass of the second additive accounts for 0.5% to 5% of the total mass of the electrolyte; for example, it is 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any value within the range of the above two-to-one values.

[0013] According to an embodiment of the present invention, the organic small molecule compound containing S and O elements is a sulfonate ester compound.

[0014] According to embodiments of the present invention, the sulfonate compound is a cyclic sulfonate compound and / or a chain sulfonate compound.

[0015] According to an embodiment of the present invention, the cyclic sulfonate compound has at least one of the structural formulas shown in Formula I and Formula II:

[0016]

[0017] In Formula I, R1 is absent or -CH2-; R2, R3, R4, R5, R6, and R7 are the same or different, and are independently selected from hydrogen, halogen, -COOH, -OCOH, substituted or unsubstituted alkyl groups; if substituted, the substituent is alkyl or halogen.

[0018] According to an embodiment of the present invention, in Formula I, R1 is absent or -CH2-; R2, R3, R4, R5, R6, and R7 are the same or different, and are independently selected from hydrogen, halogen, -COOH, -OCOH, substituted or unsubstituted C. 1-12 Alkyl; if substituted, the substituent is C. 1-12 Alkyl groups, halogens.

[0019] According to an embodiment of the present invention, in Formula I, R1 is absent or -CH2-; R2, R3, R4, R5, R6, and R7 are the same or different, and are independently selected from hydrogen, halogen, -COOH, -OCOH, substituted or unsubstituted C. 1-6 Alkyl; if substituted, the substituent is C. 1-6 Alkyl groups, halogens.

[0020] According to an embodiment of the present invention, in Formula I, R1 is absent or -CH2-; R2, R3, R4, R5, R6, and R7 are the same or different, and are independently selected from hydrogen, halogen, -COOH, -OCOH, substituted or unsubstituted C. 1-3 Alkyl; if substituted, the substituent is C. 1-3 Alkyl groups, halogens.

[0021] According to embodiments of the present invention, the cyclic sulfonate compound is selected from the following compounds:

[0022]

[0023] According to embodiments of the present invention, the chain sulfonate compound has at least one of the structural formulas shown in Formula III, Formula IV, and Formula V:

[0024] R8-S(=O)2-O-R9 Equation III

[0025]

[0026] In Formula III, R8 and R9 may be the same or different, and are independently selected from halogens, substituted or unsubstituted alkyl groups, substituted or unsubstituted alkenyl groups, substituted or unsubstituted alkynyl groups, and substituted or unsubstituted aryl groups; if substituted, the substituents are alkyl groups or halogens.

[0027] In Formula IV, M is selected from Na and K; R 10 It is selected from substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aryl, substituted or unsubstituted heterocyclic groups; if substituted, the substituent is alkyl, halogen, or heterocyclic.

[0028] According to an embodiment of the present invention, in Formula III, R8 and R9 may be the same or different, and are independently selected from halogenated, substituted or unsubstituted C. 1-12 Alkyl, substituted or unsubstituted C 2-12 alkenyl, substituted or unsubstituted C 2-12 Alkyne, substituted or unsubstituted C 6-12 Aryl; if substituted, the substituent is C. 1-12 Alkyl groups, halogens.

[0029] According to an embodiment of the present invention, in Formula III, R8 and R9 may be the same or different, and are independently selected from halogenated, substituted or unsubstituted C. 1-6 Alkyl, substituted or unsubstituted C 2-6 alkenyl, substituted or unsubstituted C 2-6 Alkyne, substituted or unsubstituted C 6-10 Aryl; if substituted, the substituent is C. 1-6 Alkyl groups, halogens.

[0030] According to an embodiment of the present invention, in Formula III, R8 and R9 may be the same or different, and are independently selected from halogenated, substituted or unsubstituted C. 1-3 Alkyl, substituted or unsubstituted C 2-3 alkenyl, substituted or unsubstituted C 2-4 Alkyne, substituted or unsubstituted C 6-8 Aryl; if substituted, the substituent is C. 1-3 Alkyl groups, halogens.

[0031] According to embodiments of the present invention, the chain sulfonate compound represented by Formula III is selected from the following compounds:

[0032]

[0033]

[0034] According to an embodiment of the present invention, in formula IV, M is selected from Na and K; R10 Selected from substituted or unsubstituted C 1-12 Alkyl, substituted or unsubstituted C 2-12 alkenyl, substituted or unsubstituted C 2-12 Alkyne, substituted or unsubstituted C 6-12 Aryl, substituted or unsubstituted 3-12 membered heterocyclic groups; if substituted, the substituent is C. 1-12 Alkyl, halogen, 3-12 membered heterocyclic groups.

[0035] According to an embodiment of the present invention, in formula IV, M is selected from Na and K; R 10 Selected from substituted or unsubstituted C 1-6 Alkyl, substituted or unsubstituted C 2-6 alkenyl, substituted or unsubstituted C 2-6 Alkyne, substituted or unsubstituted C 6-10 Aryl, substituted or unsubstituted 3-6 membered heterocyclic groups; if substituted, the substituent is C. 1-6 Alkyl groups, halogens, and 3-6 membered heterocyclic groups.

[0036] According to an embodiment of the present invention, in formula IV, M is selected from Na and K; R 10 Selected from substituted or unsubstituted C 1-3 Alkyl, substituted or unsubstituted C 2-3 alkenyl, substituted or unsubstituted C 2-3 Alkyne, substituted or unsubstituted C 6-8 Aryl, substituted, or unsubstituted 5-6 membered heterocyclic groups; if substituted, the substituent is C. 1-3 Alkyl, halogen, 5-6 membered heterocyclic groups.

[0037] According to embodiments of the present invention, the chain sulfonate compound represented by Formula IV is selected from the following compounds:

[0038]

[0039]

[0040] According to embodiments of the present invention, the sulfonate compound is selected from a combination of the compounds shown in Formula I-1 and Formula I-4. Preferably, the mass ratio of the compound shown in Formula I-1 to the compound shown in Formula I-4 is 0.8 to 1.2:1, for example, 0.8:1, 0.9:1, 1:1, 1.1:1, or 1.2:1. Studies have found that when the compound shown in Formula I-1... Compounds shown in Formula I-4 When both are added to the electrolyte as additives, their combined use produces a significant synergistic effect, resulting in the best-performing SEI film on the electrode surface and the optimal battery performance.

[0041] According to an embodiment of the present invention, the electrolyte salt is selected from lithium salts.

[0042] According to embodiments of the present invention, the lithium salt is selected from one or more of lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalate borate (LiDFOB), lithium tetrafluorooxalate phosphate (LiOTFP), lithium bis(fluorosulfonyl)imide (LiTFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluorobis(oxalate phosphate) (LiDFBP), lithium tetrafluoroborate (LiBF4), lithium bis(oxalate borate) (LiBOB), lithium hexafluoroantimonyate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium 4,5-dicyano-2-trifluoromethyl-imidazolium (LiTDI), lithium di(trifluoromethylsulfonyl)imide, lithium di(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethylsulfonyl)methyl, or lithium di(trifluoromethylsulfonyl)imide.

[0043] According to an embodiment of the present invention, the amount of electrolyte salt added is 11 to 18 wt% of the total mass of the non-aqueous electrolyte, for example, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, or 18 wt%.

[0044] According to embodiments of the present invention, the organic solvent is selected from carbonates and / or carboxylic esters, wherein the carbonate is selected from one or more of the following fluorinated or unsubstituted solvents: ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC); and the carboxylic ester is selected from one or more of the following fluorinated or unsubstituted solvents: propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, propyl propionate (PP), ethyl propionate (EP), methyl butyrate, and ethyl butyrate.

[0045] According to an embodiment of the present invention, the electrolyte is used in a lithium-ion battery.

[0046] The present invention also provides a battery comprising the electrolyte described above.

[0047] According to an embodiment of the present invention, the battery further includes a positive electrode sheet containing a positive electrode active material.

[0048] According to an embodiment of the present invention, the battery further includes a negative electrode sheet containing a negative electrode active material and a separator.

[0049] According to an embodiment of the present invention, the positive electrode sheet includes a positive current collector and a positive active material layer coated on one or both surfaces of the positive current collector, wherein the positive active material layer includes a positive active material, a conductive agent, and a binder.

[0050] According to an embodiment of the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one or both surfaces of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder.

[0051] According to an embodiment of the present invention, the mass percentage of each component in the positive electrode active material layer is: 80-99.8 wt% positive electrode active material, 0.1-10 wt% conductive agent, and 0.1-10 wt% binder.

[0052] Preferably, the mass percentage of each component in the positive electrode active material layer is: 90-99.6 wt% positive electrode active material, 0.2-5 wt% conductive agent, and 0.2-5 wt% binder.

[0053] According to an embodiment of the present invention, the mass percentage of each component in the negative electrode active material layer is: 80-99.8 wt% negative electrode active material, 0.1-10 wt% conductive agent, and 0.1-10 wt% binder.

[0054] Preferably, the mass percentage of each component in the negative electrode active material layer is: 90-99.6 wt% negative electrode active material, 0.2-5 wt% conductive agent, and 0.2-5 wt% binder.

[0055] According to an embodiment of the present invention, the conductive agent is selected from at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, metal powder, and carbon fiber.

[0056] According to an embodiment of the present invention, the adhesive is selected from at least one of sodium carboxymethyl cellulose, styrene-butadiene latex, polytetrafluoroethylene, and polyethylene oxide.

[0057] According to an embodiment of the present invention, the negative electrode active material includes carbon-based negative electrode materials and / or silicon-based negative electrode materials.

[0058] According to an embodiment of the present invention, the carbon-based anode material is selected from at least one of artificial graphite, natural graphite, mesophase carbon microspheres, hard carbon, and soft carbon.

[0059] According to an embodiment of the present invention, the silicon-based anode material is selected from at least one of silicon-oxygen anode materials or silicon-carbon anode materials, such as Si, SiC, SiOx(O) <x<2)。

[0060] According to an embodiment of the present invention, the positive electrode active material is selected from one or more of transition metal lithium oxides, lithium iron phosphate, and lithium manganese oxide; the chemical formula of the transition metal lithium oxide is Li. 1+x Niy Co z M (1-y-z) O2, where -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; where M is one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.

[0061] According to an embodiment of the present invention, the positive current collector is selected from aluminum foil, which contains Fe and Si elements, wherein the mass ratio of Fe to Si elements is ≥4.

[0062] According to an embodiment of the present invention, the presence of Fe in the aluminum foil can catalyze the formation of a passivation layer on the surface of the first additive. Specifically, the presence of Fe in the aluminum foil acts as a catalytic site, inducing the decomposition of the first additive and forming a passivation layer with FeSO4 as its main component on the aluminum foil surface. This passivation layer can significantly inhibit the catalytic oxidation and gas generation of the electrolyte on the aluminum foil surface. Simultaneously, this passivation layer can improve the battery's needle penetration performance and enhance its low-temperature performance. Research has found that Si is detrimental to the formation of a passivation layer on the aluminum foil surface by the first additive. This is mainly because the Fe content in the aluminum foil is too low, while too much Si affects the formation of the passivation layer on the aluminum foil surface, significantly deteriorating the cycle performance of the lithium-ion battery and having little effect on inhibiting gas generation. However, controlling the mass ratio of Fe to Si to ≥4 can effectively solve this problem.

[0063] The beneficial effects of this invention are:

[0064] This invention provides an electrolyte and a battery comprising the electrolyte. The introduction of a first additive with a specific ratio of O to S atoms facilitates the formation of a Li₂SO₃-based SEI film. This Li₂SO₃-based SEI film exhibits high strength and good ion conduction, improving the battery's cycle performance and storage capacity. Furthermore, it suppresses the generation of gas through redox reactions between the solvent and the positive and negative electrodes, thus enabling the electrolyte to inhibit gas production within the battery. Further, the addition of an aluminum foil with a specific Fe / Si mass ratio, containing Fe, acts as a catalytic point, inducing the decomposition of the first additive and forming a passivation layer primarily composed of FeSO₄ on the aluminum foil surface. This passivation layer significantly inhibits catalytic oxidation and gas production of the electrolyte on the aluminum foil surface. Simultaneously, this passivation layer improves the battery's needle penetration resistance and significantly enhances its low-temperature performance. In summary, by adding specific amounts of additive components and using aluminum foil with a specific Fe / Si mass ratio, a battery exhibiting superior needle penetration resistance, gas production performance, cycle performance, storage performance, and low-temperature performance can be obtained. Detailed Implementation

[0065] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are covered within the scope of protection intended by the present invention.

[0066] Unless otherwise specified, the experimental methods used in the following examples are conventional methods; unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0067] The batteries in the examples and comparative examples were prepared through the following steps:

[0068] 1) Preparation of positive electrode sheet

[0069] Lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), super P (SP), and carbon nanotubes (CNTs) were mixed in a mass ratio of 96:2:1.5:0.5. N-methylpyrrolidone (NMP) was added, and the mixture was stirred under vacuum until a homogeneous and fluid positive electrode slurry was formed. The positive electrode slurry was uniformly coated onto both surfaces of an aluminum foil (the purity of the aluminum foil is shown in Table 1, and the Fe and Si contents in the aluminum foil were further tested, with the remainder being other impurity elements such as Cu, Mn, and Ti). The coated aluminum foil was dried, and then rolled and slit to obtain the desired positive electrode sheet.

[0070] 2) Preparation of negative electrode sheet

[0071] The negative electrode active materials, artificial graphite, silicon suboxide, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP), and single-walled carbon nanotubes (SWCNTs), were mixed in a mass ratio of 79.5:15:2.5:1.5:1:0.5. Deionized water was added, and the mixture was stirred in a vacuum mixer to obtain a negative electrode active slurry. The negative electrode active slurry was uniformly coated on both surfaces of a copper foil. The coated copper foil was dried at room temperature and then transferred to an 80°C oven for 10 hours. After cold pressing and slitting, the negative electrode sheet was obtained.

[0072] 3) Preparation of electrolyte

[0073] In an argon-filled glove box (H2O < 0.1 ppm, O2 < 0.1 ppm), EC / PC / DEC / PP were mixed evenly in a mass ratio of 10 / 20 / 40 / 30. Then, 1 mol / L of fully dried lithium hexafluorophosphate (LiPF6) was quickly added, along with 5% fluoroethylene carbonate and 2% hexanetrionitrile. After dissolving, the first and second additives (1,3-propanesulfonic acid lactone) as shown in Table 1 were added. The mixture was stirred evenly, and after passing the moisture and free acid tests, the desired non-aqueous electrolyte was obtained.

[0074] 4) Battery manufacturing

[0075] The positive electrode sheet from step 1), the negative electrode sheet from step 2), and the separator are stacked in the order of positive electrode sheet, separator, and negative electrode sheet, and then wound to obtain a battery cell. The battery cell is placed in an outer packaging aluminum foil, and the non-aqueous electrolyte from step 3) is injected into the outer packaging. After vacuum sealing, settling, formation, shaping, and sorting, a battery is obtained. The charge / discharge range of the battery of this invention is 3.0-4.45V.

[0076] 5) Test methods for metallic elements in aluminum foil

[0077] Take 0.1g of foil and place it in 10mL of hydrochloric acid for at least 30 minutes (10-20% hydrochloric acid (AR) is acceptable). Then, make up to 100mL using a volumetric flask, filter the solution, and then test the ICP of the filtrate.

[0078] Table 1. Battery composition in the examples and comparative examples.

[0079]

[0080] Table 2 shows the performance test results of the batteries in the examples and comparative examples.

[0081]

[0082] Battery performance test:

[0083] (1) Cyclic performance test

[0084] The batteries of the examples and comparative examples were charged and discharged at 25°C for 100 cycles at a rate of 1C. The capacity retention rate was obtained by dividing the capacity of the 100th cycle by the capacity of the 1st cycle. The test results are recorded in Table 2.

[0085] (2) Needle puncture performance test

[0086] The batteries of the examples and comparative examples were fully charged, and then a steel needle with a diameter of 2 mm was used to puncture the battery at a speed of 100 mm / s. The results were observed to see if the battery caught fire or exploded. The test results are recorded in Table 2.

[0087] (3) Storage performance test at 60℃

[0088] The batteries of the examples and comparative examples were fully charged at 25°C, and then stored at 60°C for 35 days to observe whether gas was produced. The test results are recorded in Table 2.

[0089] (4) Low temperature test

[0090] The batteries of the examples and comparative examples were charged and discharged once at 0.2C rate at 25°C; then, the discharge capacity Q1 was recorded. They were also charged and discharged once at 0.2C rate at 0°C; then, the discharge capacity Q2 was recorded. The results are recorded as the ratio of Q2 / Q1 in Table 2.

[0091] As can be seen from Examples 1-1 to 1-6 and Comparative Examples 1 to 4 above, the electrolyte of the present invention can improve the cycle performance and storage performance of the battery, and can also suppress the generation of gas by the redox reaction between the solvent and the positive and negative electrodes, thus enabling the electrolyte to suppress gas production in the battery. This is mainly because the introduction of the first additive with a specific ratio of O atoms to S atoms is beneficial to the formation of a Li2SO3-based SEI film. This Li2SO3-based SEI film has high strength and good ion conduction performance, which can improve the cycle performance and storage performance of the battery, and can also effectively suppress the generation of gas by the redox reaction between the solvent and the positive and negative electrodes, thus enabling the electrolyte to suppress gas production in the battery.

[0092] Building upon this, aluminum foil with a specific Fe / Si mass ratio is further incorporated. The presence of Fe in the aluminum foil acts as a catalytic site, inducing the decomposition of the first additive and forming a passivation layer primarily composed of FeSO4 on the aluminum foil surface. This passivation layer significantly inhibits the catalytic oxidation and gas generation of the electrolyte on the aluminum foil surface. Simultaneously, this passivation layer improves the battery's needle penetration resistance and enhances its low-temperature performance.

[0093] As can be seen from Examples 2 to 19 above, by adding specific amounts of additive components and using aluminum foil with a specific Fe / Si mass ratio, batteries with good needle penetration performance, gas generation performance, cycle performance, storage performance and low temperature performance can be obtained.

[0094] As can be seen from Examples 20 to 22 above, when the compounds shown in Formula I-1 and Formula I-4 are added together as additives to the electrolyte, the cycle capacity retention rate and low-temperature performance of the obtained battery are significantly higher than those of other electrolytes. This may be because when the compounds shown in Formula I-1 and Formula I-4 are added together as additives to the electrolyte, the combination of the two can produce a significant synergistic effect, the SEI film formed on the electrode surface has the best performance, and the battery performance is optimal.

[0095] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An electrolyte, characterized in that, The electrolyte includes an organic solvent, an electrolyte salt, and a functional additive; the functional additive includes a first additive and a second additive, wherein the first additive is an organic small molecule compound containing S and O elements, and the ratio of the number of O atoms to S atoms in the first additive is ≤4. The organic small molecule compounds containing S and O elements are sulfonate compounds, and the sulfonate compounds include cyclic sulfonate compounds; The cyclic sulfonate compounds have at least one of the structural formulas shown in Formula I-1 and at least one of the structural formulas shown in Formula I-2: Equation I-1; In Formula I-1, R1 is either absent or -CH2-; R2, R4, and R6 may be the same or different, and are independently selected from hydrogen and -COOH; R2, R4, and R6 may not be hydrogen at the same time; R3, R5, and R7 are the same and are hydrogen. Equation I-2; In Formula I-2, R1 is either absent or -CH2-; R2, R4, and R6 may be the same or different, and are independently selected from hydrogen or halogen; R2, R4, and R6 are not all hydrogen at the same time; R3, R5, and R7 are the same and are hydrogen. The second additive is 1,3-propanesulfonate lactone; The electrolyte satisfies the following relationship: 1%≤A+B≤7%, A / B≥0.08; Wherein, A is the percentage of the mass of the first additive to the total mass of the electrolyte; B is the percentage of the mass of the second additive to the total mass of the electrolyte.

2. The electrolyte according to claim 1, characterized in that, A ranges from 0.5% to 4%.

3. The electrolyte according to claim 1 or 2, characterized in that, B is 0.5%~5%.

4. The electrolyte according to claim 1, characterized in that, The sulfonate compounds further include chain sulfonate compounds, which have at least one of the structural formulas shown in Formula III, Formula IV, and Formula V: R8-S(=O)2-O-R9 Equation III [M + [O - -S(=O)2-R 10 Formula IV Formula V In Formula III, R8 and R9 may be the same or different, and are independently selected from halogens, substituted or unsubstituted alkyl groups, substituted or unsubstituted alkenyl groups, substituted or unsubstituted alkynyl groups, and substituted or unsubstituted aryl groups; if substituted, the substituents are alkyl groups or halogens. In Formula IV, M is selected from Na and K; R 10 It is selected from substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted aryl, substituted or unsubstituted heterocyclic groups; if substituted, the substituent is alkyl, halogen, or heterocyclic.

5. The electrolyte according to claim 1, characterized in that, The sulfonate compounds are selected from a combination of the compounds shown in Formula I-3 and Formula I-4; Formula I-3 Formula I-4.

6. The electrolyte according to claim 5, characterized in that, The mass ratio of the compound shown in Formula I-3 to the compound shown in Formula I-4 is 0.8 to 1.2:

1.

7. A battery, characterized in that, The battery comprises the electrolyte according to any one of claims 1-6.

8. The battery according to claim 7, characterized in that, The battery further includes a positive electrode sheet containing positive electrode active material. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on one or both surfaces of the positive electrode current collector. The positive electrode active material layer includes positive electrode active material, conductive agent and binder. The positive electrode current collector is selected from aluminum foil, which contains Fe and Si elements, wherein the mass ratio of Fe to Si elements is ≥4.

Citation Information

Patent Citations

  • Nonaqueous electrolyte solution for batteries and lithium secondary battery

    CN107534185A

  • Electrolyte functional additive, non-aqueous lithium ion battery electrolyte containing the additive and lithium ion battery

    CN109088100A

  • Electrolyte containing silicon solvent and sulfonate-class additive and lithium ion battery using electrolyte

    CN109802178A

  • Electrochemical device and electronic device comprising same

    CN113078362A

  • Lithium ion battery

    CN114068936A